Pemurnian Bioetanol Menggunakan Adsorben Silika Gel dari Limbah Botol Kaca di Industri Kecap - Adhi Setiawan; Achmad Fatoni; Tarikh Azis Ramadani (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2022)
Waste glass bottles is an inorganic waste that amounts to 0.7 million tons per year with the main content of silica, so it can be used as the main ingredient to produce silica gel. In the soy sauce industry, glass bottle waste is generally produced from broken glass bottles during depalletizer activity, namely the activity of moving glass bottles to the glass bottle cleaning area. The glass bottle waste is generally only accommodated and has not been used optimally. This research aims to utilize waste glass bottles as a raw material for producing silica gel adsorbents using the hydrothermal method and the sol-gel approach. Silica gel becomes an adsorbent in the purification of bioethanol from wastewater washing dissolving tanks using the adsorption method. Variations in the bioethanol production are yeast weight as 0, 2, 5, and 8 g as well as fermentation time for 4, 7, and 10 days. The bioethanol purification process used variations in adsorption time for 40, 60, and 80 minutes. Characterization of silica gel using BET and SEM-EDX test. Bioethanol levels after going through the adsorption process were analyzed using the GC-MS method. The BET test results show that activated silica gel has a surface area of 231,851 m2/g. Analysis with SEM-EDX showed that activated silica gel particles were in the form of porous lumps with chemical content of Si and O elements of 40.94% and 51.92%, respectively. Based on the results of the GC-MS test, 60 minutes is the best adsorption time to increase the bioethanol content from 39,8 % to 72,0 %.